Quantity of antibiotic use and its association with clinical outcomes in COVID-19 patients: A snapshot from a provincial referral hospital in Indonesia - Yossadania, Asyriva; Hayati, Zinatul; Harapan, Harapan; Saputra, Irwan; Mudatsir, Mudatsir; Diah, Muhammad; Ramadhana, Ika F. (Narra Sains Indonesia, 2023)
Irrational antibiotic use in Indonesia is considered high, yet there are still lacks reliable information regarding the issue. The quantity of antibiotic use studies, in particular during coronavirus disease 2019 (COVID-19) pandemic, was not well reported. The aim of this study was to evaluate antibiotic use in COVID-19 patients at a province referral hospital in Aceh, Indonesia, Dr Zainoel Abidin Hospital, and to assess the association between antibiotic use and COVID-19 clinical outcomes. The defined daily dose (DDD) method was used and expressed in DDDs per 100 patient-days as in hospital setting. The data were obtained from inpatient confirmed COVID-19 patients between March 2020 and December 2021. A logistic regression was used to determine the association between patients’ characteristics and antibiotic usage with clinical outcomes. A total of 361 treated COVID-19 patients were included using a random sampling technique and analyzed. Out of 361 patients, 89.2% of them were treated with antibiotic(s). All the antibiotics were given empirically except for cefazoline (5.5%) that was used as prophylaxis to obstetric patients who underwent the c-section. Azithromycin was the most prescribed antibiotic and levofloxacin had the highest DDD. Our data suggested that there was no association between antibiotic use and clinical outcomes of COVID-19 patients (p=0.128). Having sepsis and another pulmonary disease however were associated with mortality of COVID-19 patients with adjusted odds ratio (aOR) 14.14; 95%CI 2.94–67.90, p=0.001 and aOR 8.64; 95%CI 3.30–22.63, p<0.001, respectively. In addition, patients older than 60-year-old had a higher chance to an unfavorable outcome compared to those younger than 30-year-old, aOR: 7.61; 95%CI: 1.07–53.94. In conclusion, the use of antibiotics is prevalent among COVID-19 and it is not directly associated with clinical outcomes.